Pengaruh Child Abuse Dalam Keluarga Terhadap Perkembangan Sosial Anak Usia Dini - Hasanah; Hulailah Istiqlaliyah (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
The purpose of this research is to find out how far the influence and how big the relationship is between child abuse in the family and the social development of early childhood. In line with the formulation of the problem, this type of research is quantitative with a correlation approach. Data collection uses a questionnaire made in the form of Googleform. The sample studied was 50 parents using purposive sampling. And research analysis by passing a series of statistical tests to a simple linear regression test and ending with drawing conclusions. Based on the theory and results of analysis through the interpretation of statistical data it proves that H0 is accepted and Ha is rejected. Thus, it is known that child abuse in the family has a significant influence on the social development of early childhood at a significance level of 0.05 (5%). The correlation value obtained was 0.299, which means that the correlation between child abuse in the family and early childhood social development was 29.9%, indicating that there was a significant relationship. The percentage contribution to the influence of the variable child abuse in the family is sufficient, therefore child abuse in the family quite influences the social development of early childhood. The percentage of child abuse variable in the family is 29.9% which shows that child abuse in the family is quite influential. While the remaining 71.1% is influenced by other factors.